Effectiveness of two different splints to treat temporomandibular disorders - (:unkn) unknown (URBAN & VOGEL, 2015)
Nearly 5% of the the world's population has temporomandibular disorder (TMD) severe enough to make them seek treatment. A third of the total population has at least one TMD symptom. There are different types of splints to treat TMD. In our study, we compared the success of two different appliances [stabilization splint (ss), nociceptive trigeminal inhibition splint (NTI)] by using Fonseca's questionnaire, the OHQoL-UK and visual analog scale (VAS). A total of 40 patients suffering from TMD were included in this study and answered questionnaires twice, at the beginning of the treatment and 3 months later. Regarding TMD alone, 39 patients (97.5%) had some degree of the disorder, 7 of of these cases being mild (17.5%), 15 moderate (37.5%), and 17 severe (42.5%). We analyzed posttreatment changes compared to baseline. Pain complaints decreased in both groups, and the OHQoL-UK revealed better quality of life after treatment. Based on the posttreatment Fonseca's questionnaires, significant changes in the patients' complaints in the group SS (p < 0.01) were observed. The group NTI also displayed changes but these were not statistically significant after treatment (p > 0.05). Patients in both groups had fewer TMD complaints after TMJ treatment. According to the Fonseca's questionnaire, the patients' major TMD complaint was clenching-grinding, followed by pain in the craniomandibular joint, or earache.
Keywords: Splint; Temporomandibular joint disorders; Bruxism; Pain; Questionnaires; QUALITY-OF-LIFE; ORAL-HEALTH; ELECTROMYOGRAPHIC ACTIVITY; STABILIZATION SPLINT; MYOFASCIAL PAIN; OCCLUSAL SPLINT; THE-LITERATURE; SLEEP BRUXISM; SYMPTOMS; MUSCLES